Distributive justice : who gets what and how - Sulaiman, Kabuye Uthman (Sultanbeyli Belediyesi, 2012)
Distribution of wealth and income is one of the most important topics concerning the economic life of man, and yet the most controversial. It is due to distribution of wealth and income that great revolutions such as the French Revolution of 1789, and armed conflicts in many parts of the world have taken place. The most fundamental question in the distribution of wealth and income is: What criterion or criteria should be followed to achieve distributive justice? This question has been a big controversy among philosophers, economists, and politicians, and no conclusion has ever been reached. The aim of this paper is to analyze the principles of distributive justice according to Islam and liberal thought. It focuses on the views of Sayyid Qutb, ;-"luhammad Baqir al-Sadr, John Rawls and Robert J\ozick. The former two are recognized figures in the contemporary Islamic thought. They have addressed themselves to social, political, cultural and economic problems prevalent among contemporary Muslims and have suggested some ways to overcome them, based on the teachings of the Qur'all and SW11lah. They are regarded among the pioneers of Islamic revival, which is concerned mainly with the establishment of an Islamic State, and the application of the Shari'aTr (Islamic la",,") in all aspects of life. The latter two are contemporary American philosophers who have contributed new ideas to the conception of justice. No study of justice is considered complete without reference to their views